Protective effects of flavonoid-rich extracts from Hibiscus sabdariffa leaves on streptozotocin-induced testicular damage in rats - Ajiboye, Basiru Olaitan; Famusiwa, Courage Dele; Falode, John Adeolu; Okwukwe, Akojuru Daniel; Owolabi, Bamikole Tosin; Adejumo, Adedeji A.; Oyinloye, Babatunji Emmanuel; Ajuwon, Olawale Razaq; Ogedengbe, Oluwatosin Olalekan; Ojo, Oluwafemi Adeleke (Elsevier BV, 2025)
Objective: This study investigated the protective effects of flavonoid-rich extracts from Hibiscus sabdariffa leaves on testicular cumulative reproductive function biomarkers in streptozotocin (STZ)-induced diabetic rats.
Methods: Rats were induced with 40 mg/kg body weight (bwt) STZ intraperitoneally (i.p.), after which they were administered either a low (150 mg/kg bwt) or a high (300 mg/kg bwt) dose of flavonoid-rich extracts from H. sabdariffa leaves. Testicular redox biomarkers, reproductive hormone biomarkers, and relative gene expression levels of PDE-5 and iNOS were assessed. Additionally, histological data, glucose levels, G6PDH activity, and hydroxysteroid dehydrogenase activities (3β-HSD and 17β-HSD) were analyzed.
Results: H. sabdariffa leaf extract was promising for restoring redox balance, normalizing reproductive hormone levels, modulating gene expression, and regulating various biochemical parameters related to testicular function.
Conclusion: These data suggest a potential therapeutic role of H. sabdariffa leaves in mitigating the testicular dysfunction associated with diabetes.